On Critical Frameworks for Analyzing Indigenous Literature: The Case of Monkey Beach - Lacombe, Michèle (International Journal of Canadian Studies / Revue internationale d’études canadiennes)

(untitled) (Conseil international d'études canadiennes, 2010)
AbstractTeachers and critics who include best-selling novels by Indigenous writers in discussions of Canadian literature are contributing to the wider circulation of those novels, which can only be beneficial. Nevertheless, the tendency to read these novels using methods derived from Euro-Canadian cultural and literary frameworks, while useful, is in many ways limiting. Critical methods emerging from Indigenous intellectual, cultural, and academic contexts can enrich our readings of such work, as well as lead us to the discovery (or recovery) of related Indigenous literature that does not achieve such wide circulation. This essay focuses on a few different ways of reading Eden Robinson’s well-known novel Monkey Beach, arguing that paying attention to a diversity of methodologies within Indigenous literary theory can enrich the reading experience. Two prominent schools of thought, here understood as complementary rather than in opposition, and both finding their origins in American Indian rather than Native Canadian interdisciplinary studies, are Indigenous literary nationalism and trickster discourse as it intersects with notions of hybridity. Focussed on Nation-specific uses of creation stories in cultural revitalization, and on urban “post-indian” perspectives respectively, these approaches offer alternatives to prevailing Western approaches such as ethnographic, magic realist, or gothic readings.